The Governance Role of Audit Committees: Reviewing a Decade of Evidence. (30th August 2012) - Ghafran, Chaudhry; O'Sullivan, Noel
<x xml:space="preserve">Abstract</x> Even though audit committees have traditionally been a key component of corporate governance regulation, the last decade has witnessed a greater emphasis on audit committee regulation and a parallel intensification of academic research on the subject. This review synthesizes recent empirical research seeking to investigate various aspects of audit committees' governance role. The review is structured around current regulatory expectations of audit committees seeking to document the extent to which specific characteristics of good practice influence various components of audit committee effectiveness. It is found that larger and more independent audit committees as well as those with financial expertise are more likely to seek a higher level of external audit coverage and assurance. There is also evidence that more independent audit committees are associated with the purchase of lower levels of non‐audit services from auditors, thereby seeking to preserve the independence of the external audit process. There seems a consensus that more independent audit committees and those with greater accounting/financial expertise have a positive impact on the quality of financial statements. Evidence on the stock market reaction to audit committee issues suggests that investors both welcome the presence of audit committees and react positively when members are appointed with relevant expertise. It is also found that internal auditors view certain audit committee characteristics, specifically independence, expertise and frequency of meetings, as leading to more effective audit committee performance. In summary, therefore, this review documents a significant amount of evidence offering support to current regulations concerning the desired characteristics of audit committees.